THE EFFECTS OF SIDE FRICTION REDUCTION TO THE PERFORMANCE OF UNSIGNALIZED INTERSECTION (CASE STUDY IN BANDUNG, INDONESIA) - Anastasia Caroline Sutandi; Novaliya Novaliya (Journal of Civil Engineering, 2009)
Unsignalized intersections, which are locations, with high potential traffic congestion, are the largest number of intersections in large cities in developing country such as Indonesia. Moreover, a number of side frictions worsen traffic congestion and then decrease performance of intersection. Some Regulator traffic signs have been installed to reduce traffic congestion at these locations. However, road users especially angkot (local public transportation mode) drivers ignored the signs. The purpose of this paper is to analyze the effects of side friction reduction to the performance of the intersection. Unsignalized intersection at Rajawali-Dadali in Bandung, Indonesia was used as a case study. Results of this paper showed that at the intersection with capacity of around 4000 pcu/hour, degree of saturation of 0.91 and delay of 15.3 second/pcu, traffic signs alone were not effective. The presence of police officer increased 8.46 percent of capacity, decreased 2.72 percent of degree of saturation, and decreased 4.93 percent of delay at the intersection. However, since the presence of police officers are not always available even during peak hours, it is recommended that the unsignalized intersections with high degree of congestions be changed into signalized intersections.